1994
DOI: 10.1128/aem.60.6.2101-2106.1994
|View full text |Cite
|
Sign up to set email alerts
|

Effect of a Pseudomonas rhamnolipid biosurfactant on cell hydrophobicity and biodegradation of octadecane

Abstract: In this study, the effect of a purified rhamnolipid biosurfactant on the hydrophobicity of octadecane-degrading cells was investigated to determine whether differences in rates of octadecane biodegradation resulting from the addition of rhamnolipid to four strains of Pseudomonas aeruginosa could be related to measured differences in hydrophobicity. Cell hydrophobicity was determined by a modified bacterial adherence to hydrocarbon (BATH) assay. Bacterial adherence to hydrocarbon quantitates the preference of c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
111
0
2

Year Published

1997
1997
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 351 publications
(119 citation statements)
references
References 20 publications
(18 reference statements)
4
111
0
2
Order By: Relevance
“…Candidate molecules are biosurfactants. P. aeruginosa can produce biosurfactants, among them are rhamnolipids, which have been reported to modulate and shear parts of its cell surface to adapt to certain environmental cues (Zhang and Miller, 1994;Al Tahhan et al, 2000). To characterize this P. aeruginosa-derived shedding factor, it was precipitated upon acidification of the culture filtrates, chemical properties characteristic for rhamnolipids (Rahman et al, 2002).…”
Section: Hbd-2-and Il-8-inducing Supernatants Of P Aeruginosa Contaimentioning
confidence: 99%
“…Candidate molecules are biosurfactants. P. aeruginosa can produce biosurfactants, among them are rhamnolipids, which have been reported to modulate and shear parts of its cell surface to adapt to certain environmental cues (Zhang and Miller, 1994;Al Tahhan et al, 2000). To characterize this P. aeruginosa-derived shedding factor, it was precipitated upon acidification of the culture filtrates, chemical properties characteristic for rhamnolipids (Rahman et al, 2002).…”
Section: Hbd-2-and Il-8-inducing Supernatants Of P Aeruginosa Contaimentioning
confidence: 99%
“…Cell hydrophobicity was analyzed by a modi¢ed method to monitor bacterial adhesion to hydrocarbons [23]. One ml of cells grown in minimal salts M9 medium with hexadecane as the carbon source was centrifuged and the cells resuspended in 1 ml of minimal salts medium.…”
Section: A¤nity Of Cells For the Organic Phasementioning
confidence: 99%
“…increase the hydrophobicity) in the molecule, and the occurrence of branched polymers, particularly those that contain two or three sugars in the branching unit [12,15,251. Species of Acinetobacter have been reported as possessing hydrophobic cell surfaces 128, 291, and it has been suggested that a hydrophobic cell surface may be a requirement for the enhanced biodegradation of carbon substrates [30], and the production of surface activity [3 11. Thus, the occurrence of hydrophobic 0-antigens and LPS in Acinetobacter is consistent with the production of surfaceactive molecules [32-341 and growth on hydrophobic substrates [35 -371.…”
Section: Sugarmentioning
confidence: 99%